2021
DOI: 10.1097/qai.0000000000002776
|View full text |Cite
|
Sign up to set email alerts
|

Poorer Muscle Quality and Quantity With ART Initiation Is Associated With Greater Inflammation and Immune Activation

Abstract: Background:We have previously shown that the initiation of antiretroviral therapy (ART) is associated with a decrease in skeletal muscle density (greater fat accumulation), suggesting that gains in lean body mass seen in many ART studies may reflect gains in low quality, fatty muscle. Here, we explore whether skeletal muscle density and area are associated with markers of inflammation and immune activation.Methods: ART-naïve people with HIV were randomized to raltegravir or ritonavir-boosted atazanavir or daru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…56 Among PWH initiating ART, both baseline and change in muscle density and area were associated with greater inflammation. 13 Consistent with the existing literature, in this study, we found strong correlations between muscle density and greater hs-CRP, MCP-1, sTNFR-1, and IIS and correlations between muscle area and greater MCP-1. MCP-1, particularly, is a cytokine that may play a key role in mitochondrial signaling and muscle damage/repair.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…56 Among PWH initiating ART, both baseline and change in muscle density and area were associated with greater inflammation. 13 Consistent with the existing literature, in this study, we found strong correlations between muscle density and greater hs-CRP, MCP-1, sTNFR-1, and IIS and correlations between muscle area and greater MCP-1. MCP-1, particularly, is a cytokine that may play a key role in mitochondrial signaling and muscle damage/repair.…”
Section: Discussionsupporting
confidence: 92%
“…We have previously shown that HIV, in addition to increasing age, may be an important contributor to declines in muscle density and area. 12–16 The health consequences associated with lower muscle density are less well-described, particularly in muscle groups beyond the trunk and thigh, although deposition of ectopic fat in other tissues (eg, liver and pericardium) can have a detrimental impact on cardiometabolic disease risk, driven in part by inflammation. 17…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the authors postulated that this may be due to fatty muscle, as evidenced by the decreased muscle density, despite similar CSA [12]. Decreased muscle area has been associated with increased inflammatory markers, immune system activation and cardiovascular disease [15, 59] We did not identify studies using CT to quantify the amount of total skeletal muscle mass among PWH.…”
Section: Historical and Present Utility Of Skeletal Muscle Imaging Am...mentioning
confidence: 99%
“…This may be due, in part, to ART use and changes in fat distribution (i.e. lipodystrophy) and it has been linked to increased inflammation [14–18].…”
Section: Introductionmentioning
confidence: 99%